1972
DOI: 10.1084/jem.135.6.1228
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Recognition and the Immune Response

Abstract: Based on the original observation that L-tyrosine-azobenzene-p-arsonate (RAT) I induced specific delayed hypersensitivity in guinea pigs (1), we have shown that this small molecule could serve as a carrier for a macromolecular hapten (2). Conjugates of RAT and poly-3'-n-glutamic acid (PGA) raised humoral antibody specific for the PGA determinant and cellular immunity directed against the RAT determinant in guinea pigs. In addition, prior immunization with RAT potentiated the anti-hapten response (2). These obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

1972
1972
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…DISCUSSION" RAT is probably the smallest molecule which has been shown to be immunogenic and, as such, offers an excellent model for study of the immune response at molecular and cellular levels. It has been shown that RAT can serve as a carrier for haptens (2,3), and bifunctional antigen molecules have been fabricated to explore various molecular parameters of the immune response such as minimum essential spacing of determinants and the capacity to induce "selfhelp": the cooperation of an immunogenic determinant in the humoral response to a second identical determinant (3). In addition, the antihapten antibodies produced in response to small bifunctional antigens appear to be substantially less heterogeneous by isoelectric focusing than antibodies provoked by conventional hapten-protein conjugates (Roelants, G. E., and J. W. Goodman, unpublished observations), suggesting that RAT may have general utility as a carrier for the preparation of relatively homogeneous anti-hapten antibody of virtually any specificity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DISCUSSION" RAT is probably the smallest molecule which has been shown to be immunogenic and, as such, offers an excellent model for study of the immune response at molecular and cellular levels. It has been shown that RAT can serve as a carrier for haptens (2,3), and bifunctional antigen molecules have been fabricated to explore various molecular parameters of the immune response such as minimum essential spacing of determinants and the capacity to induce "selfhelp": the cooperation of an immunogenic determinant in the humoral response to a second identical determinant (3). In addition, the antihapten antibodies produced in response to small bifunctional antigens appear to be substantially less heterogeneous by isoelectric focusing than antibodies provoked by conventional hapten-protein conjugates (Roelants, G. E., and J. W. Goodman, unpublished observations), suggesting that RAT may have general utility as a carrier for the preparation of relatively homogeneous anti-hapten antibody of virtually any specificity.…”
Section: Resultsmentioning
confidence: 99%
“…Modifications at the arsonate position yielded immunogens with distinctive specificities (3). Preliminary findings with compounds modified at the tyrosine position indicated that one, but not both, charged groups were essential for immunogenicity (3).…”
Section: Received For Publication 25 May 1972)mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of stearylamine-containing liposomes with glutaraldehyde provides reactive groups suitable for linkage of synthetic peptides and at the same time increases the rigidity of the lipid membranes. Such liposomes, especially when containing carrier function-enhancing RAT sites (Alkan et al, 1971(Alkan et al, , 1972, appear to be a promising tool for preparing fully synthetic immunogens for eliciting antiviraI antibodies.…”
mentioning
confidence: 99%
“…Included among these are the minimum separation between haptenic and carrier determinants required for an anti-hapten antibody response and whether "self-help," the capacity of an immunogenic determinant to cooperate in the humoral response to a second identical determinant, is possible (3). Asymmetric bifunctional molecules consisting of one RAT determinant and one dinitrophenyl (DNP) determinant separated by spacers of various size consistently induced anti-DNP antibody and cellular immunity specific for the RAT group (3). On the other hand, symmetrical bifunctional molecules composed of two RAT determinants separated by the same spacers were unable to provoke either primary or secondary anti-RAT humoral responses (3), although it is well known that the arsonate group is a potent hapten.…”
mentioning
confidence: 99%